Effects of packaging on the storage stability of flat piaya treated potassium sorbate and antioxidants - Amigo, Ronald Ladrillo
Flat piaya treated with potassium sorbate and antioxidants packed in oriented polypropylene (Lot 1), metalized bag (Lot 2), and vacuum bag (Lot3 were characterized based on their physical properties and proximate composition and investigated for storage stability at room conditions (28-32 degree celcius) for forty-nine days.